Evaluation of Radical Scavenging and Antioxidant Activities of Trahydrocurcumin An In vitro and In vivo Study - Pari, Leelavinothan (International Journal of Pharmaceutical & Biological Archive, 2013)
Evaluation of Radical Scavenging and Antioxidant Activities of Trahydrocurcumin An In vitro and In vivo Study